Bioinspired redox-coupled conversion reaction in FeOOH-acetate hybrid nanoplatelets for Na ion battery. Issue 34 (16th August 2022) - Park, Bum Chul; Cho, Jiung; Zhang, Jiliang; Amedzo-Adore, Mawuse; Lee, Dae Beom; Kim, Sung-Chul; Bae, Jong Seong; Uhm, Young Rang; Kim, Sang-Ok; Koo, Jehyoung; Kang, Yong-Mook; Kim, Young Keun
Abstract : FeOOH complexed with acetate exploits the stepwise intercalation/conversion and biotic Fe redox, enabling a highly reversible conversion reaction. FeOOH reduction coupled with acetate oxidation after Na ion intercalation gives a solid framework for stable Na ion storage. Abstract : The considerable interest in rechargeable batteries is causing a rapid increase in demand and a surge in the price of raw materials. Earth-abundant iron oxyhydroxide (FeOOH) is a promising candidate as an anode material for sodium-ion rechargeable batteries (SIBs). However, the application of FeOOH is hindered by numerous technical limitations arising mainly from the irreversibility of the conversion reaction. Here, we manipulate biotic Fe redox from FeOOH-acetate hybrid nanoplatelets (FAHPs) to make the resulting conversion reaction with Na ions highly reversible. The extended lepidocrocite-type FAHP, in which FeOOH and acetate components are stacked in a layer-by-layer assembly, undergoes facile initial intercalation owing to its large interlayer spacing. Consequently, the redox reaction coupled with FeOOH reduction and acetate oxidation occurs in a similar way to the biotic Fe redox reaction. During the subsequent discharge–charge cycles, carbonate produced by the redox coupling of acetate and FeOOH serves as a stable and reversible host for Na ion storage. This study establishes a novel method for enabling highly reversible conversion reactions and enhancing the electrochemical capacity using not only Na ions but Li ions through the exploitation of the interplaying redox of inorganic and organic materials in hybrid structures.